2011
DOI: 10.1128/aac.01243-10
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mutations in a Patient Isolate of Streptococcus agalactiae with Reduced Penicillin Susceptibility Emerging after Long-Term Oral Suppressive Therapy

Abstract: Penicillin nonsusceptibility has been demonstrated in group B streptococci (GBS), but there is limited information regarding mechanisms of resistance. We report a case of GBS with reduced susceptibility to penicillin emerging after long-term suppressive oral penicillin therapy for a prosthetic joint infection. Molecular characterization of the isolate before and after long-term penicillin therapy revealed 5 mutations in the ligand-binding regions of PBP1a, -2a, and -2x not previously reported in GBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
51
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 16 publications
2
51
1
2
Order By: Relevance
“…In particular, substitutions of Val405Ala and/or Gln557Glu of PBP2X correlated with increases in the MIC, indicating a reduced PEN susceptibility. Elsewhere, PRGBS possessing substitutions of PBPs (PBP1A, PBP2A, PBP2B, and PBP2X) were isolated from adult patients in Canada (9,10) and the United States (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, substitutions of Val405Ala and/or Gln557Glu of PBP2X correlated with increases in the MIC, indicating a reduced PEN susceptibility. Elsewhere, PRGBS possessing substitutions of PBPs (PBP1A, PBP2A, PBP2B, and PBP2X) were isolated from adult patients in Canada (9,10) and the United States (11).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, PRGBS isolates were found to possess various PBPs (PBP1A, PBP2A, PBP2B, and PBP2X) among isolates from adult patients in Canada (9,10) and the United States (11).…”
mentioning
confidence: 99%
“…revious published reports have shown that group B Streptococcus (GBS) isolates were 100% susceptible to both penicillin (1, 2) and vancomycin (1); however, reduced susceptibilities to penicillin have been documented (3)(4)(5)(6)(7)(8). GBS susceptibilities to clindamycin and erythromycin have varied (2,(9)(10)(11)(12), and data regarding inducible clindamycin resistance are not always reported (2).…”
mentioning
confidence: 99%
“…Besides these two key substitutions, multiple amino acid substitutions were also found in PBP 2X, PBP 2B, and PBP 1A among PRGBS isolates, depending on the penicillin MIC levels (6)(7)(8). After our aforementioned study, PRGBS isolates harboring amino acid substitutions in PBPs were also reported in the United States and Canada (9)(10)(11). The prevalence of penicillin nonsusceptibility among GBS isolates from various clinical sources has increased from around 4.5% between 2007 and 2012 to 6.6% in 2013, according to the Japan Nosocomial Infections Surveillance (JANIS) of the Ministry of Health, Labour and Welfare (see http://www.nih-janis.jp).…”
mentioning
confidence: 91%
“…PRGBS isolates were reported in the United States and Canada after our first investigation of their emergence and molecular mechanisms, but they are still rare (6)(7)(8)(9)(10)(11). Domestically, our subsequent investigations revealed the increase of PRGBS among clinical GBS isolates, their tendency toward resistance to multiple drugs, and a probable association of such a multidrug-resistant PRGBS clone with nosocomial spread (16).…”
mentioning
confidence: 99%